“I'm Not Good Enough for Anyone”: Legal Status and the Dating Lives of Undocumented Young Adults - Pila, Daniela (Sociological Forum, 2016)
The impact of legal status on romantic relationships has not been adequately explored in the literature. Based on video and phone interviews with 25 undocumented activists from the ages of 18 to 28 years old, this research examines how legal status affects the romantic relationships of undocumented women and men. The hegemony of traditional dating scripts made it difficult for those without legal status to participate. Gender roles were consistent with stereotypical male and female roles in dating, which often attribute more power and responsibility to men. As such, women experienced a slight advantage because traditional notions of courtship did not require them to provide the resources required for dating, such as money or transportation, which in contrast were commonly expected of the men. In contrast, women noted the difficulties of disclosing their legal status and depending on their partners for everyday activities. Additionally, both men and women faced exclusion that inhibited their dating lives, as a direct result of their legal status. This suggests that the impact of legal status may be salient at all stages of family formation and that undocumented young adults are experiencing a distinct phenomenon compared to their documented and native-born peers.
Keywords: citizenship; dating; dept.soc; immigration; legality; undocumented; young adults

Ph.Dead - Bloch, Jon P. (Pegasus Books, 2016)
Keywords: College stories; dept.soc; faculty_collection

Is Fifty Really the New Thirty? The Stigma of Age as a Form of Strain and its Role in Drug and Alcohol Abuse and Dependence by Women - Black, Pamela; Brown, Alan D. (Deviant Behavior, 2016)
Aging bodies stigmatize women. The effects of stigma, health issues, goal disappointment, and a combination of age and minority group status, overwhelm older women's coping strategies, leading to maladaptive behaviors. General strain theory posits a relationship between negative stimuli and deviant behavior. Advancing age and age-related stigma reflect this strain. This study explores the relationship between strain and substance abuse or dependence, comparing subsamples of middle age (35- to 49-year-old women) and older middle age (50- to 64-year-old) women. Data suggest that minority age status coupled with acute or mental health issues increase substance abuse or dependence by older women.
Keywords: dept.soc

Organizing lesbian/queer bathhouse events: Emerging forms of sexual experience. - Brown, A D; Gailey, Nerissa (Journal of Lesbian Studies, 2016)
Discussions of public sexual spaces in the social science literature have, until recently, been dominated by analyses of men's use of these spaces for erotic expression. In the late 1990s, feminist collectives began to explore the emancipatory potentials these spaces can have for lesbian sexualities. After a police raid on one such event called the "Pussy Palace," scholars in diverse disciplines began to explore how these events have both opened up and restricted erotic possibilities for lesbians, queer women, and trans* attendees. This article reviews the existing social science literature on lesbian and queer bathhouse events and highlights several key themes and subthemes that have dominated the discourse, including the importance that these spaces be recognized for their ability to both shape and be shaped by principles of community, safety, and sexual health/wellness.
Keywords: *Homosexuality, Female; *Homosexuality, Male; *Public Facilities; *Sexual Behavior; Baths; Female; Homosexuality, Female; Homosexuality, Male; Humans; Lesbian; Male; Public Facilities; Sexual Behavior; Social Behavior; bath; bathhouse; dept.soc; ethic of care; female; human; lesbianism; male; male homosexuality; public sex; sanitation; sexual behavior; sexual politics; social behavior

Beyond either/or: Reading trans* lesbian identities. - Gailey, Nerissa; Brown, A D (Journal of Lesbian Studies, 2016)
Previous research has explored the affiliation and distancing strategies employed in published memoirs of gender transition. In this article, we are particularly interested in elucidating the ways in which individuals construct identities and characterize their sexualities, and how sociohistorical constraints might influence what is expressed with respect to this in personal narratives of transition. Using the memoirs of Lili Elbe (Hoyer, 1933) and Joy Ladin (2013) as conceptual brackets, this article investigates the complex relationship between the development and articulation of trans* identities and lesbian sexualities within the context of published memoirs of gender transition.
Keywords: *Homosexuality, Female/px [Psychology]; *Transgender Persons/px [Psychology]; Female; Gender Identity; Homosexuality, Female; Humans; Lesbian; Male; Personal Narratives as Topic; Sex Reassignment Surgery; Sex Reassignment Surgery/px [Psychology]; Transgender Persons; Women's Rights; dept.soc; female; feminist movements; gender identity; human; identity; lesbianism; literature; male; memoirs; psychology; sex reassignment; sexuality; trans*; transgender; women's rights

“A grain of salt in a pepper shaker”: interviewing whites, blacks, and latinos about their neighborhood preferences - Meyerhoffer, Cassi A (Sociological Forum, 2016)
Several perspectives dominate as explanations for neighborhood preferences: pure race, racial proxy, race-based neighborhood stereotyping, and race-associated neighborhood factors. This analysis extends and supports the pure race and race-associated neighborhood factors arguments by showing that these theories are applied differently depending on respondents' social class, race and ethnicity, and whether they are talking about white, black, or Latino neighborhoods. Race-associated factors are emphasized for white and black neighborhoods, but pure race serves as a better theoretical framework for understanding people's preferences for Latino neighborhoods. I analyze qualitative interview data, using maps of real neighborhoods and hypothetical neighborhood show cards, to examine the neighborhood preferences of 65 white, black, and Latino residents in Ogden, Utah, and Buffalo, New York.
Keywords: African Americans; Latinos; dept.soc; neighborhood racial association; pure race; racial proxy; racial residential segregation